MODEL PENYESUAIAN DIRI MAHASISWA YANG MENGIKUTI PROGRAM MBKM - Siti Nurhidayah; Ratna Duhita Pramintari; Fithria Ikhlasiyah Az Zahra (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45 Bekasi, 2022)
This study aims to determine the effect of self leadership and interpersonal communication on self adjustment with self efficacy as a mediator. This study uses quantitative method with a correlational research design and path analysis. This subjects in this study were 118 students at the Islamic University “45” Bekasi. The measurement instrument uses a psychological scale consisting of a self leadership scale with an r alpha value= 0,889, an interpersonal communication scale with an r alpha value= 0,830, a self adjustment scale with an r alpha value= 0,807, and a self efficacy scale with an r alpha value= 0, 829. The sampling technique used is random sampling. The data analysis tecnique used Spearman’s Rho Correlation and Path Analysis. This study found that there was a positive relationship self leadership with self adjustment (r=0,332, p<0,05), interpersonal communication with self adjustment (r=0,720, p<0,05), self leadership with self efficacy (r=0,399, p<0,05), interpersonal communication with self efficacy (r=0,658, p<0,05), and self efficacy with self adjustment (r=0,625, p<0,05). From the results of the path analysis test, it was found that self leadership and interpersonal communication were able to directly or indirectly influence self adjustment by involving self efficacy as a mediator.